2002
DOI: 10.1542/peds.110.2.e23
|View full text |Cite
|
Sign up to set email alerts
|

Weight Criticism During Physical Activity, Coping Skills, and Reported Physical Activity in Children

Abstract: ABSTRACT. Objective. National health guidelines advocate increased physical activity in children and adolescents, but specific goals are not being achieved. Data are needed on variables that influence children's decision to be active or sedentary.Methods. We tested the association of weight criticism during physical activity (WCA) with attitudes toward physical activity and reported physical activity levels in children. We also tested whether these associations were moderated by children's ability to cope with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
260
3
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(287 citation statements)
references
References 47 publications
12
260
3
7
Order By: Relevance
“…There is evidence that the experience of being victimized by peers can lead overweight children to avoid taking part in activities, such as physical education classes or sports, to avoid peer victimization [51]. Our findings suggest that the social context can also affect time engaged in eating-versus playing-related activities.…”
Section: Discussionmentioning
confidence: 64%
“…There is evidence that the experience of being victimized by peers can lead overweight children to avoid taking part in activities, such as physical education classes or sports, to avoid peer victimization [51]. Our findings suggest that the social context can also affect time engaged in eating-versus playing-related activities.…”
Section: Discussionmentioning
confidence: 64%
“…Faith found that children who are criticized for their weight by their parents or by other children are less likely to enjoy sports, and less likely to participate in mild-intensity leisure activity. 64 Thus, plausible mechanisms exist for reverse causation in the relation of physical activity and weight status.…”
Section: Physical Activity and The Development Of Obesitymentioning
confidence: 99%
“…13 Its negative implications include impairments in psychological well-being [14][15] and physical health, such as avoiding preventive health-care services, 16 engaging in unhealthy eating patterns 13,[17][18][19] and avoiding physical activity. 18,[20][21][22] Despite evidence of weight bias documented in case studies, experimental work, treatment and convenience samples, limited information is available on the prevalence and patterns of weight discrimination in a nationally representative sample. Discrimination is distinct from prejudice and beliefs in that it refers to negative, unequal treatment of people because of their membership in a particular group.…”
Section: Introductionmentioning
confidence: 99%